(untitled) (Journal of the College of Education for Women, 2019)
The aim of the present research is to know the following : What are the Science and technology, society and environment issues (S.T.S.E) which included in the content of thechemistry Book second grade intermediate ? And to achieve the objective of search The two researchers has prepares a list of science and technology, society and environment issues (STSE) consisted of (9) key issues namely (Air quality and the atmosphere, sustainable development, water security, health and preventive security, mineral resources investment, pollution of various kinds, energy, food industry, production of weapons technology) and from which (70) sub-issues emerge,Arbitrators competent agreement has been received . Then, thetwo researchers analyzed the content of the chemistry booksecond grade intermediate in the academic year (2015-2016) depending on the prepared list of the(S.T.S.E), was assured of the validity and reliability, The results showedThe chemistry booksecond grade intermediate achieved (17) sub-issue with percentage of (24.29%) . In the light of the search results, the two researchers recommend Including chemistry booksecond grade intermediate with main and sub- main issues of the (S.T.S.E) issues that have not been included , as one of the important modern attitudes in the scientific education , the researcher suggested to conducting other studies to analyze chemistry books for the other stages, and other subjects such as physicsin the light of the same issues .